Development of Tissue Culture Textbook Based on Project Based-Learning to Improve Science Process Skills of Biology Department Students Universitas Negeri Medan - Harahap, Salamah; Harahap, Fauziyah; Hasanah, Dwi; Sembiring, Gres Anjelia; Panggabean, Syakilah Kurnia Fahmi; Nadhilla, Annisa; Suriani, Cicik; Edi, Syahmi; Daulae, Abdul Hakim (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The research on the development of this textbook was carried out based on the results of the analysis of student needs, namely that there are no teaching materials that can improve students’ science process skills in the Tissue Culture course at the Department of Biology, State University of Medan. This textbook is compiled based on the learning syntax of Project-Based Learning (PjBL). This study aims to develop a Project-Based Learning-based tissue culture textbook to improve students’ science process skills. This research method uses the Research and Development (R&D) with Thiagarajan’s 4D (Define, Design, Develop, and Disseminate). The population of this study was students of the Biology Department of Universitas Negeri Medan with a sample of 47 people who were given a PjBL-based tissue culture textbook. The results showed that (1) the textbooks have been tested for feasibility by material experts (87,73) (2) instructional design experts (92) with a very feasible category, (3) the response of tissue culture lecturers (92) and (4) students based on individual tests (95.1), small group tests (93,75), and limited group tests (90.02) with a very good category and (5) the results of the calculation of N-Gain for science process skills were obtained at 0.66 which is in the medium category.